2017
DOI: 10.1002/gcc.22477
|View full text |Cite
|
Sign up to set email alerts
|

Copy number alterations determined by single nucleotide polymorphism array testing in the clinical laboratory are indicative of gene fusions in pediatric cancer patients

Abstract: Gene fusions resulting from structural rearrangements are an established mechanism of tumorigenesis in pediatric cancer. In this clinical cohort, 1,350 single nucleotide polymorphism (SNP)-based chromosomal microarrays from 1,211 pediatric cancer patients were evaluated for copy number alterations (CNAs) associated with gene fusions. Karyotype or fluorescence in situ hybridization studies were performed in 42% of the patients. Ten percent of the bone marrow or solid tumor specimens had SNP array-associated CNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The examples include the fusion between the MLLT10 gene in 10p12.3 and KMT2A gene in 11q23 [94], and the fusion between the ETV6 gene in 12p13.2 and the ABL1 gene in 9q34.12 [95]. Generation of such fusions occurs through complex rearrangements with multiple breakpoints and is often accompanied by non-specific abnormalities in the karyotype; CNAs mapping to the breakpoints within the partner genes are frequent in these cases, and can be detected by CMA [26,30,49,91].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The examples include the fusion between the MLLT10 gene in 10p12.3 and KMT2A gene in 11q23 [94], and the fusion between the ETV6 gene in 12p13.2 and the ABL1 gene in 9q34.12 [95]. Generation of such fusions occurs through complex rearrangements with multiple breakpoints and is often accompanied by non-specific abnormalities in the karyotype; CNAs mapping to the breakpoints within the partner genes are frequent in these cases, and can be detected by CMA [26,30,49,91].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…If only one of the derivative chromosomes from a clinically important translocation is present in the karyotype, the abnormality may be difficult to recognize by conventional cytogenetic analysis. However, the resulting copy number imbalance with the breakpoints mapping within the fusion partner-genes make such abnormalities easily recognizable by CMA [91]. Table 1.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These studies provided some biologic evidence for the role played by MAML2 in possible molecular mechanisms of carcinogenesis. A recent study showed that the CRTC1-MAML2 gene fusion was also identified in the brain tumors [23]. Additionally, MAML2 as a novel gene was abnormal expressed in glioma [14].…”
Section: Discussionmentioning
confidence: 99%
“…In precision medicine, heritable genetic variations of subjects are assessed to determine whether they have a high risk of developing cancer [ 22 ]. Among various genetic variations, SNPs have been relatively well associated with developing breast cancer, glioma, or leukemia along with other forms of cancer [ 22 , 23 , 24 , 25 , 26 ]. The risk of cancer caused by these SNPs is heritable, accounting for approximately 10% of all cancer cases [ 27 , 28 ].…”
Section: The Path That Precision Oncology Has Takenmentioning
confidence: 99%